ANALISIS GEOMEKANIKA 1D UNTUK PENENTUAN STABILITAS LUBANG SUMUR DI LAPANGAN TIMUR, CEKUNGAN JAWA TIMUR, JAWA TIMUR - Kiki R Siagian, F
This study is located at Timur Field, East Java Basin. The stratigraphy of the Timur Field consists of Tuban, Ngrayong, Wonocolo, Ledok, Mundu and Lidah formations which are Early Miocene to Pleistocene in age. The proposes of this study are to estimate insitu stress, determine 1D geomechanic model, determine safe mud weight while drilling at certain azimuth and inclination, and analyse the relationship between geomechanical model and geological condition in the study area. The analysis was performed in four wells (LT-1, LT-2, LT-3, and LT-4) at Timur Field, by using gamma ray, density, and sonic logs, image log (FMI), pressure data, and well report. Based on data processing and analysis in four wells, it is known that average gradients of horizontal stress (SHmax) 1.1 -1.14 psi / ft, minimum horizontal stress (Shmin) 0.95 -1.04 psi / ft, and vertical stress 0.89 - 0.94 psi / ft. The direction of maximum horizontal is northeast – southwest, and stress regime changes from strike silp fault to reverse fault, when entering overpressure zone. The minimum mud weight can be applied if wellbore azimuth is parallel to the maximum horizontal stress (N 350 E and N 2150 E). The width of mud window is narrower as inclination is increasing (0-90 0).